Maternal risk factors and microbiological profile of urinary tract infections in pregnancy: a cross-sectional study at a tertiary care center - Akansha Goyal; Sapna Chauhan (MGM Journal of Medical Sciences, 2025)
Introduction: Urinary tract infections (UTIs) in pregnancy are a significant cause of maternal and fetal morbidity, necessitating early detection and targeted management. Despite extensive research, gaps remain in understanding the interplay of demographic, obstetric, and clinical risk factors influencing UTI susceptibility. This study aims to assess the prevalence of symptomatic and asymptomatic bacteriuria (ASB), identify associated risk factors, and analyze the distribution of bacterial uropathogens in pregnant women. By refining risk stratification, the findings contribute to enhancing antenatal screening protocols and guiding evidence-based preventive strategies to reduce UTI-related complications during pregnancy. Aim: To assess the prevalence, risk factors, and bacterial distribution of UTIs in pregnancy. Objectives: 1.Determine the prevalence of symptomatic and ASB. 2.Analyze maternal demographic, obstetric, and clinical risk factors. 3.Identify bacterial uropathogens and their distribution. 4.Provide insights for improved antenatal screening and prevention. Materials and Methods: A cross-sectional study was conducted among 600 pregnant women and categorized into symptomatic (n = 400) and asymptomatic (n = 200) groups. Sociodemographic characteristics, obstetric risk factors, and clinical parameters were assessed. Midstream urine samples were collected for culture, and bacterial isolates were identified using standard microbiological methods. Data were analyzed using the chi-square test, and statistical significance was set at P < 0.05. Results: The overall prevalence of UTI was 17.3% (104/600), with a significantly higher occurrence in the symptomatic group (66.3%) compared to the asymptomatic group (33.7%) (P < 0.001). The highest prevalence was observed among multigravida women (56%). Significant risk factors for UTI included lower socioeconomic status, rural residence, history of previous UTI, diabetes, and anemia (P < 0.05). Among bacterial isolates, Escherichia coli (56%) was the most common uropathogen, followed by Enterococcus spp. (15%), Klebsiella pneumoniae (11.5%), and Pseudomonas spp. (11.5%). Conclusion: This study highlights the significant burden of UTIs in pregnancy and their association with key demographic and clinical risk factors. The findings emphasize the need for routine screening and early management, particularly in high-risk groups, to prevent adverse maternal and neonatal outcomes. Integrating targeted preventive strategies into antenatal care can help mitigate the impact of UTIs, improving maternal health outcomes.